A Spanner in the Works? Anti-Politics in Global Health Policy; Comment on "A Ghost in the Machine? Politics in Global Health Policy" - David McCoy; Guddi Singh (Kerman University of Medical Sciences, 2014)
The formulation of global health policy is political; and all institutions operating in the global health landscape are political. This is because policies and institutions inevitably represent certain values, reflect particular ideologies, and preferentially serve some interests over others. This may be expressed explicitly and consciously; or implicitly and unconsciously. But it's important to recognise the social and political dimension of global health policy. In some instances however, the politics of global health policy may be actively denied or obscured. This has been described in the development studies literature as a form of 'anti-politics'. In this article we describe four forms of anti-politics and consider their application to the global health sector.